Associations between cyberbullying perpetration and the dark triad of personality traits: the moderating effect of country of origin and gender. Issue 3 (2nd July 2020) - Wright, Michelle F.; Huang, Zheng; Wachs, Sebastian; Aoyama, Ikuko; Kamble, Shanmukh; Soudi, Shruti; Li, Zheng; Lei, Li; Shu, Chang
ABSTRACT: This study's aim was to investigate the associations among narcissism, Machiavellianism, callous and unemotional traits, and cyberbullying perpetration among 1, 637 adolescents ( M age = 13.53 years, 48% girls overall) from China, India, and Japan. Adolescents completed questionnaires on the dark triad of personality traits, and cyberbullying and face-to-face bullying perpetration. Narcissism and callous and unemotional traits were related to cyberbullying perpetration for Chinese and Indian adolescents, as was Machiavellianism for Indian adolescents. Gender did not moderate these associations. Our findings suggest the need to monitor the dark triad of personality traits and for prevention programmes against cyberbullying to consider the cultural context.